FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR DI BEI - Dwiaknita Nandia Fatmasari, 09.05.52.079; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2013)
This study aims to empirically examine the factors that affect the capital structure of the company by using the analyzed variables are firm size (SIZE), asset structure (SA), profitability (NPM), sales growth (GROW) and managerial ownership(MAN). The sample in this study is a joint Food and Beverages manufacturing sectors listed on the Indonesia Stock Exchange (IDX) of the years 2007-2011. The results of this study indicate that company size (SIZE) and no significant positive effect on capital structure, asset structure (SA) have positive and significant impact on capital structure, profitability (NPM) and a significant negative effect on capital structure, as well as sales growth (GROW ) and managerial ownership (MAN) and no significant negative effect on the capital structure of the company manufacturing the Food and Beverages sector listed on the Indonesia Stock Exchange in 2007-2011. Keywords: Firm Size (SIZE), Asset Structure (SA), Profitability (NPM), Sales Growth (GROW),Managerial Ownership (MAN) and Capital Strukture (DER).